Analysis and mining of L-ornithine L-aspartate adverse events based on FAERS database - Hui Zhang; Chaoqun Song; Dexi Zhao; Minghao Lin; Yujuan Fu (Scientific Reports)
Abstract L-ornithine L-aspartate (LOLA) is indicated for reducing blood ammonia levels and alleviating symptoms of hepatobiliary disorders. Data mining of adverse events associated with LOLA was carried out in the FDA Adverse Event Reporting System database. The aim was to explore its potential medication risks and offer more reasonable and safe references for clinical medication. This study retrieved and extracted adverse event reports related to LOLA from the FAERS database from 2004Q1 to 2024Q3. The main method utilized was the reporting odds ratio for the detection of risk signals related to LOLA. In total, 413 adverse event reports where LOLA was the primary suspect drug were recognized, and a sum of 670 adverse events were reported. These reports mainly came from patients aged 40–65 and older. Most of these reports were submitted by healthcare professionals. After screening LOLA, 323 positive risk signals for AEs were found, which were distributed across 25 system organ classes. Among these, hepatobiliary disorders topped the list. Specifically, 84 positive risk signals were identified for liver-related AEs, which is in line with the adverse reactions about LOLA published by the FDA. The risk of hepatobiliary disorders was not described in the manual, but this study found that the positive signal risk for the hepatobiliary system is the highest. This research underscores the substantial influence of LOLA on hepatobiliary disorders, stressing the necessity for vigilant monitoring of potential liver toxicity. Besides concentrating on the short-term adverse reactions after LOLA administration, it is also crucial to conduct in-depth research on its long-term safety. This study provides suggestions and directions for the rational and safe clinical application of LOLA. Prospective studies in the future are required to further investigate the occurrence of relevant adverse events.